Analysis of pharmacological aspects involving the treatment of postpartum depression: a systematic review (Research, Society and Development, 2022)
Although depression can start at any age, most women develop these affective disorders postpartum. Postpartum depression is a depressive disorder that occurs when typical depressive episodes appear during the puerperium. It belongs to the puerperal psychiatric syndrome, which is the same as postpartum restlessness and postpartum psychosis. The objective of this article is to discuss the pharmacological aspects and pharmaceutical performance in the management of patients with Postpartum Depression. This is a systematic review, of a qualitative nature, with exploratory objectives, using studies published between 2014 and 2022 in the SCIELO, LILACS and VHL databases as data collection instruments. The descriptors were used: “PPD”, “Postpartum Depression” and “Postpartum Depression Treatment”. Studies indicate that puberty, premenstruation, pregnancy, puerperium and menopause have always raised speculations about the weight of psychosocial and biological factors and their possible interactions in the chain of causes of psychiatric diseases that occur in a temporal connection, as in the gestational processes in women. women. Postpartum depression in particular raises the question of its specific etiology and therapy. Postpartum depression in particular raises the question of its specific etiology and therapy. It is concluded that although antidepressants are contraindicated in postpartum women, their non-administration brings more serious effects to the health of the mother and her baby. As a result, pharmaceutical monitoring is required as a way of mitigating the effects on patients with PPD.